The bloody spur - Spillane, Mickey, 1918-2006; Collins, Max Allan (A Caleb York western, 2018)
"Rancher George Cullen doesn't like the Santa Fe Railroad's plan to drive a spur through his town. He intends to put up a fight--even though everyone else in Trinidad, New Mexico, including his own daughter, stands on the side of the railroad ... Sheriff Caleb York rides out to the Bar-O to reason with his old friend. But Cullen's ex-partner, Burt O'Malley, is back in town after a twenty-year stint in the pen. And hired gun Alver Hollis, aka the Preacherman, has shown up with two cronies, claiming they're in town for a big poker game. With the whole town on the verge of a shootout, Caleb keeps a firm grip on his Colt .44. Soon enough, he'll take dead aim to keep the peace."--Page 4 cover